2021
DOI: 10.1111/aos.14757
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG capsulotomy is not a risk factor for retinal detachment after phacoemulsification cataract surgery

Abstract: Purpose To evaluate the cumulative incidence and risk factors of pseudophakic retinal detachment (PRD) following phacoemulsification cataract surgery. Methods Cataract surgeries performed between the years 2007 and 2016 at the Ophthalmology Unit of Kymenlaakso Central Hospital, Kotka, Finland, were included. The cumulative incidence of PRD was estimated through Kaplan–Meier analysis. Patient mortality was incorporated as one of the censoring events. Cox regression analyses were used to evaluate potential risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, there are Nd:YAG laser posterior capsulotomy complications, such as elevation of IOP, 3 intraocular lens damage, 7 iritis and anterior chamber haemorrhage. 8 , 9 Increased IOP develops in more than half of the patients after laser treatment. However, this increase is usually below 30 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are Nd:YAG laser posterior capsulotomy complications, such as elevation of IOP, 3 intraocular lens damage, 7 iritis and anterior chamber haemorrhage. 8 , 9 Increased IOP develops in more than half of the patients after laser treatment. However, this increase is usually below 30 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eligible studies, 4 reported HRs for pseudophakic RD after Nd:YAG capsulotomy using Cox proportional hazards models, representing a total of 175 pseudophakic RD cases in 42 079 eyes undergoing cataract surgery. 13,15,19,21 Among them, 4427 eyes underwent Nd:YAG laser capsulotomy. As the heterogeneity of the study results was marginal (I 2 = 53%, P = .09), a fixed-effects model was applied.…”
Section: Hr Of Nd:yag Capsulotomy For Pseudophakic Rdmentioning
confidence: 99%
“…However, other studies did not suggest a causal relationship between Nd:YAG capsulotomy and the risk for developing RD. 8,9,11,14,17,20,21 Moreover, Elbaz et al recently reported the largest retrospective cohort study based on case records. 21 In 17 688 eyes that underwent phacoemulsification performed between 2007 and 2018, 83 laterality-matched eyes developed subsequent RD (incidence of 0.11% per year).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior capsule opacification 44,45 Capsule opacification If associated with a decrease in visual acuity or there if there is a change in quality of vision, then a YAG capsulotomy should be performed.…”
Section: Complication Symptom(s) Treatmentmentioning
confidence: 99%